Care and treatment of hepatitis C among Aboriginal people in New South Wales, Australia: implications for the implementation of new treatments. Issue 1 (2nd January 2016) - Treloar, Carla; Jackson, Clair; Gray, Rebecca; Newland, Jamee; Wilson, Hannah; Saunders, Veronica; Johnson, Priscilla; Brener, Loren
Abstract : Introduction. Despite Aboriginal Australians being over-represented in populations of people living with hepatitis C (HCV), there is a dearth of research to guide policy and programme development in the area of care and treatment, particularly relating to new HCV treatments. Method. In-depth interviews were conducted with 39 people identifying as Aboriginal Australians and living with HCV in New South Wales. Results. Participants' experiences were characterised by a lack of detailed or appropriate information provided at diagnosis, high levels of stigma associated with HCV and low overall knowledge of HCV as reported for themselves and their communities. Despite poor diagnosis experiences, participants had undertaken changes to their lifestyle, especially in relation to alcohol use, in order to promote liver health. Concerns about treatment side effects and efficacy impacted participants' decisions to undertake treatment. Eleven participants had undertaken HCV treatment in a variety of care models with a peer worker and in prison. Conclusions. The similarities between concerns and experiences of Aboriginal people and other populations living with HCV do not suggest that services and strategies to engage these populations should also be the same. These results suggest that further engagement of the primary care sector in HCV care is important as well as increasing Aboriginal community knowledge of HCV. A variety of service models should be available to meet individuals' preferences, including those offered within Aboriginal community controlled health services emphasising holistic notions of health, and supported by information and communication programmes using principles of health literacy relevant to Aboriginal people.